(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article describes the role and importance of interregional tax inspection in the improvement of large-scale reforms aimed at creating favorable conditions for conducting business activities in tax areas in the country, further strengthening the confidence of business circles. At the same time, some important reforms in the tax system of Uzbekistan, which are being implemented in the organization of neighborhood work, have been studied, and scientific and practical conclusions and proposals have been developed on foreign experience and its application in our country.